Formulation and biochemical evaluation of designer diet enriched with botanicals for bone health - Ammara Yasmeen (Food Science & Nutrition, 2020)
Abstract The study designed to evaluate the role of sesame, fenugreek flax, and nuts seeds as best alternatives for therapeutic agents to improve bone mineral status. Effect of these plant seeds on proximate composition, antioxidant potential, mineral, fatty acid, and amino acid profile of supplements was studied. The sesame, fenugreek, and flaxseeds were incorporated with nuts at level of 35% to develop supplement. Improved contents of protein, fat, and NFE were recorded in range of 25.72–32.23, 18.92–23.15, and 34.25%–39.59%, correspondingly. The antioxidant potential of supplements is high (450.56 mg GAE/ 100g) prepared with fenugreek followed by flaxseeds and sesame seeds. Calcium as fundamental bone mineral found greater (525.15%–790.21%) in seed‐based supplement. Enhanced contents of Oleic, linoleic, and linolenic acids ranged 17.32–41.78, 21.72–44.23, and 1.00%–47.12%, respectively. Nutritional enriched supplements may be best alternatives for improving bone health by lowering osteoclast and increasing osteoblast mechanism in bone development.